Household inventions - Clemons, L. Ethel (My University, 1905)
Introduction: It is within relatively a few years that inventions to be used in the home have received any important consideration. Comparing the household with other industries it has been obviously belated in labor-saving devices. Farming has been made more successful by science and invention; the life of the agriculturist has been changed from that of drudgery to one of progressive enterprise, and "the evolutions and revolutions in commerce and manufactures are truly marvelous". It is true that much work has gone out of the house to be done by machines at the factory. However until about the middle of the nineteenth century the housewife had to do her own spinning, weaving and dyeing and each girl of the family had to weave the linen for her future use. As the kitchen is the room in which the woman of the house spends a large portion of her time, it is a room worthy of careful consideration. "While the parlor is the crown of the home, the kitchen is the heart". "As the heart by its ceaseless throbbing sends the streams of life through every part of the human system carrying disease or health, so the influence from the kitchen brings to the entire household weal or woe". The first kitchen of which we have record was that of the savages. It was the forest with a mat of leaves for a floor and the sky as a roof. The usual modes of cooking were either by placing the victuals in the ashes, on heated tones, or by braising them on sticks over the fire, while the few utensils used were of the crudest handmolded pottery. The Egyptian kitchen was a large circular room which was used for all purposes. In the center of the room was built a large fireplace and as there was no chimney the smoke had to escape through any outlet that it could penetrate.
Citation: Clemons, L. Ethel. Household inventions. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Fireplce Replaced Cook Stove; Tin Cans and Stone Jars for Storage; Kitchen Cabinet; Theses